Phytochemical Richness vs. Antimicrobial Efficacy: Interrogating the Discordance in Musa Acuminata Leaf Extracts against Common Pathogens (E. Coli & S. Aureus) - Dr. Tirthkumar B. Patel MD; Dr. Rushil Vaid MD; Dr. Arpan P. Patel MD; Joseph P. Bendo (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Antibiotic resistance continues to out pace the discovery of new drugs, renewing interest in plant derived antimicrobials. Musa acuminata (banana) has a long record in ethnomedicine, yet data on its leaf metabolites and antibacterial potential remain limited. Methods: Fully expanded leaves were collected in Cavite, Philippines, authenticated, air dried and pulverised. Crude ethanolic extracts (CEE) were obtained by maceration and subsequently fractionated by column chromatography with ethyl acetate, acetone and methanol. Qualitative phytochemical tests and thin layer chromatography (TLC) established chemical fingerprints. Antibacterial activity of CEE and solvent fractions (0.5 mL; equivalent to 50 mg mL ¹) was determined against Staphylococcus aureus ATCC 25923 and Escherichia coli ATCC 25922 using broth microdilution minimum inhibitory concentration (MIC) assays. Results: CEE contained alkaloids (+), terpenoids (+), and abundant flavonoids, saponins, tannins, and cardiac glycosides (+++). TLC corroborated these findings (distinctive orange, violet blue and brown spots under specific reagents, Rf 0.42–0.78). None of the solvent fractions achieved visible growth inhibition at the tested concentration; MIC values therefore exceeded 50 mg mL ¹ for both organisms. Literature comparisons indicate that higher doses or alternative extraction protocols (e.g. stem or peel) have shown activity in related Musa taxa. Conclusion: M. acuminata leaves are rich in bioactive secondary metabolites, yet the ethanolic leaf extract and its polarity guided fractions were inactive against S. aureus and E. coli at ≤ 50 mg mL ¹. Future work should increase assay concentrations, employ bio guided purification to isolate individual phenols and flavonoids, and broaden the pathogen panel to include multidrug resistant strains.